From Bio-glass to Low-Softening Temperature Glasses: A Comprehensive Exploration of Glass Varieties - Gaur, Aadarsh (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 6 No 2 (2023): Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
This article delves into the multifaceted realm of glass, exploring its diverse applications across various industries. From the revolutionary Bio-glass with its biocompatible properties transforming medical technology, to the innovative automotive glasses enhancing safety and comfort on the road, the discussion encompasses decorative glasses, organic glasses, inorganic glasses, new inorganic glasses, sol-gel glasses, and low-softening temperature glasses. Each type of glass is examined for its unique characteristics and applications, showcasing the evolving nature of this versatile material. As we navigate through the intricacies of glass science and technology, it becomes evident that the world of glass is not only enduring but continuously pushing the boundaries of innovation in materials science and